FinTech and Financial Inclusion: Exploring the Mediating Role of Digital Financial Literacy in Enhancing Access to Financial Services - Adhikari, Madhav; Ghimire, Dinesh Mani; Lama, Anil Dong (Journal of Emerging Management Studies, 2024)
Purpose – With consideration for the mediating function that digital financial literacy plays in the region, the study's goal is to determine how FinTech adoption may promote financial inclusion in the Kathmandu Valley. The three original constructs of the unified theory of acceptance and use of technology (UTAUT), namely performance expectancy (PE), effort expectancy (EE), and social influence (SI), were integrated with three additional factors - trust (TR), perceived security (PS), and service quality (SQ) of the Value-based Adoption Model (VAM), to create a conceptual framework. Design/methodology/approach – A quantitative method was employed to gather data from 312 FinTech users through the use of a cross-sectional questionnaire. Microsoft Excel and the SPSS software were used to examine the data. The research designs used were correlational and causal comparative. Findings – The findings revealed that FinTech use has a significant correlation between each variable. Also, TR, SQ, PS, PE, and EE have a substantial impact on the adoption of FinTech use. While SI doesn’t have a substantial impact on the adoption of FinTech services. Additionally, the study shows that DFL has a mediating role in FU and FI. Conclusion – This study provides significant details on the complex relationship between FinTech adoption and financial inclusion and demonstrates how FinTech adoption increases people's access to formal financial services, which in turn promotes financial inclusion. Along with highlighting its significance in the possible expansion of FinTech usage, the study also emphasizes the mediating role that digital financial literacy plays. Implications – Policymakers and FinTech service providers may find this study useful in better understanding the relatively low adoption rate of FinTech and in creating plans to increase user acceptance in the Kathmandu Valley. Originality – This study contributes to the exploration of FinTech's potential to promote financial inclusion with a focus on the mediating role of digital financial literacy in Nepal’s Kathmandu Valley.